An annotated checklist of the birds of the Tanimbar Islands - Bishop, K David; Brickle, Nick W (KUKILA, 1998)
Wallacea, after years of seeming ornithological neglect, has recently come to the fore (see White & Bruce 1986, Coates & Bishop 1997). Since about 1981 there has been an increasing number of bird watchers and expeditions to the region resulting in the rediscovery of a number of 'feared extinct' and little known species. Most of the islands or island groups have by now received at least a cursory visit during the last 17 years. As a result many species previously known only from collections have been rediscovered, and others thought to be threatened have, thankfully, been shown not to be (see Coates & Bishop 1997). One of, the few exceptions to this coverage is the Tanimbar Islands.